The Effect of Eye-Feedback Training on Orienting Attention in Young Adults With Sluggish Cognitive Tempo - Kim, Kiho; Lee, Youna; Lee, Jang-Han (Frontiers in Psychiatry, 2020)
Sluggish cognitive tempo (SCT) is a kind of attentional symptoms characterized by symptoms of slowness in behavior or in thinking. The aim of the present study was to develop a preliminary attention training program based on real-time eye-gaze feedback using an eye-tracker. A total of 38 participants with SCT were randomly assigned to one of following two conditions: eye-feedback (N = 19; Mean Age = 21.21; range 18 - 26) or control (N = 19; Mean Age = 20.68; range 18 - 25). The participants in the eye-feedback condition received three repeated trainings on the modified version of the Posner’s spatial cueing test; we also used real-time constant eye-gaze feedback designed to lead the participants to quickly and accurately engage and to disengage, with pre- and post- measurement of eye-movements (overt attention) and the revised attention network test (ANT-R; covert attention). The participants in the control condition received three repeated same trainings without any feedback, with pre- and post-measurement of eye-movements measure and ANT-R. The results revealed that the eye-feedback group showed a greater improvement in engaging and disengaging attention through the overt attention measure than the control group. The eye-feedback group also showed a greater increase only in the orienting network related to disengaging attention in the covert attention measure compared to the control group. These results suggested that the eye-feedback can be meaningfully used in attention training to enhance the efficiency of attention in clinical settings.